Prevalence of chromosomal abnormalities identified by copy number variation sequencing in high-risk pregnancies, spontaneous abortions, and suspected genetic disorders. Issue 3 (March 2019) - Zhang, Rui; Chen, Xiangbin; Wang, Dong; Chen, Xuan; Wang, Chao; Zhang, Yuhong; Xu, Mengnan; Yu, Jingcui
Objective: High-throughput sequencing based on copy number variation (CNV-seq) is commonly used to detect chromosomal abnormalities including aneuploidy. This study provides evidence for the prevalence of chromosomal abnormalities in target populations. Methods: A total of 160 samples, including 83 high-risk pregnancies, 37 spontaneous abortions, and 40 suspected genetic disorders, were analyzed by CNV-seq. Relationships between the incidence of these chromosomal abnormalities and risk factors (e.g. advanced maternal age, abnormal pregnancy history, and family history of congenital disease) were further analyzed by subgroup. Results: A total of 37 (44.6%) high-risk pregnancies, 25 (67.6%) spontaneous abortions, and 22 (55%) suspected genetic disorders had chromosomal abnormalities including aneuploidy and CNVs. There was an increased risk association between the prevalence of aneuploidy and pathogenic-relevant CNV in the fetus or abortive tissue and advanced maternal age. Moreover, a family history of congenital disease was also positively correlated with fetal chromosomal abnormalities in high-risk pregnancies. Conclusion: A relatively high prevalence of chromosomal abnormalities was detected in high-risk pregnancies, spontaneous abortions, and suspected genetic disorders, indicating the importance of CNV detection in such populations.